Vaccine Adjuvants - Ibrahim Mohamed Saeed Shnawa (Vaccines and Vaccine Interference, 2023)
Adjuvants are heterogeous chemical compounds having the potential to highthen the immune responses when incorporated, preconditioned or added post priming with antigens. There are T cell dependent, and T independent adjuvants. The classical adjuvants are water-in-oil with or without microbial fraction, the Freund adjuvants. The immune adjuvanicity can be mediated by several immune mechanisms.